Exploring UK Knife crime and its associated factors: A content analysis of online newspapers - Kabir, Russell; Vinnakota, Divya; Rahman, Q.M.; Sathian, Brijesh; Bai, Ancy Chandrababu Mercy; Deividas, Nikulin; Pellissery, Maneesha-Varghese; Kareem, Sajna Kizhackanaly Abdul; Hasan, Md. Rakibul; Parsa, Ali Davod (Nepal Journal of Epidemiology, 2022)
Background: Knife crime has become a common phrase used by the media, but it is not always clear what it refers to or what they mean when they use the term. Knife crime can cover many offences, making it challenging to define and estimate its prevalence. Methods Six UK online news portals were purposefully chosen to be included in the study, and knife crime news was searched retrospectively. Because English is the country's official language, only English online news portals were chosen. The term "knife crime" was used to search. The news portals were the: Metro, the Sun, the Guardian, Daily Mail, Daily Mirror and the Evening Standard. Retrospectively, news portals were initially searched with the search term Results In the assigned news portals, 692 reports were found between January 2011 and December 2021. The study revealed that the 11-20 years of age group individuals are more vulnerable as victims, and males are more reported as victims when compared to females. About 61.8% of knife crimes are reported from South England. Conclusion Knife crime risk is higher in early adulthood and among males. Street violence, fights/gang attacks, family issues and robbery are the leading causes of knife crime and have all been identified as risk factors that must be addressed with caution.